Pembatasan Sosial Berbasis Kelurahan (PSBK) Dalam Penanganan Covid-19 Kota Bima Ditinjau Dari Perspektif Hukum - Munir, Munir; Sukirman, Sukirman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to determine and understand whether PSBK is by the provisions of the legislation and to determine the impact of PSBK implementation in Bima City. The nature of the research is empirical legal research. The approach used is interdisciplinary. The data sources are sourced from primary legal materials, secondary legal materials, and tertiary legal materials. The results of the study show that there is a discrepancy between PSBK and statutory regulations, namely, the legislation only recognizes PSBB and does not recognize PSBK as in Law Number 6 of 2018 concerning Health Quarantine and in Regulation of the Minister of Health Number 9 of 2020 concerning PSBB Guidelines, then there is a lack of synchronization. , comprehensive disharmony and multiple interpretations between Law Number 4 of 1984 concerning Outbreaks of Infectious Diseases and Government Regulation Number 40 of 1991 concerning Management of Outbreaks of Infectious Diseases, and Law Number 24 of 2007 concerning Disaster Management. Furthermore, there are impacts caused by the PSBK both legally, economically, and socially.